EFFECTIVE WAY OF FORMING CONSTRUCTION TERMINOLOGY DATABASE (KONFERENSIYA, 2025)
This thesis focus on some effective principles and ways of forming andconstruction terminology database. Two principles are discussed throughthesis:pespective and descriptive way which are considered as main principles notonly construction terminoloy but also word forming and systematizing lexic-semanticfields